2021
DOI: 10.3390/ijms222111615
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Contribution to Warfarin-Induced Arterial Media Calcification in Mice

Abstract: Arterial media calcification (AMC) is predominantly regulated by vascular smooth muscle cells (VSMCs), which transdifferentiate into pro-calcifying cells. In contrast, there is little evidence for endothelial cells playing a role in the disease. The current study investigates cellular functioning and molecular pathways underlying AMC, respectively by, an ex vivo isometric organ bath set-up to explore the interaction between VSMCs and ECs and quantitative proteomics followed by functional pathway interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The fact that carotid segments of animals exclusively treated with warfarin did not show an altered ACh relaxation compared with carotid segments of control animals, indicate that the stimulated NO response was intact. Compromised basal NO release together with an intact receptor‐stimulated NO response was also seen earlier in organ chamber experiments using aortic segments of Fbn1C1039G/+ (Marfan model) mice, 39 apolipoprotein E‐deficient mice, 40 stroke‐prone spontaneously hypertensive rats 41 and warfarin fed DBA/2J mice 16 …”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The fact that carotid segments of animals exclusively treated with warfarin did not show an altered ACh relaxation compared with carotid segments of control animals, indicate that the stimulated NO response was intact. Compromised basal NO release together with an intact receptor‐stimulated NO response was also seen earlier in organ chamber experiments using aortic segments of Fbn1C1039G/+ (Marfan model) mice, 39 apolipoprotein E‐deficient mice, 40 stroke‐prone spontaneously hypertensive rats 41 and warfarin fed DBA/2J mice 16 …”
Section: Discussionsupporting
confidence: 64%
“…Compromised basal NO release together with an intact receptor-stimulated NO response was also seen earlier in organ chamber experiments using aortic segments of Fbn1C1039G/+ (Marfan model) mice, 39 apolipoprotein E-deficient mice, 40 stroke-prone spontaneously hypertensive rats 41 and warfarin fed DBA/2J mice. 16 Western blot results showed that eNOS and p-eNOS expression in the infrarenal aorta of L-NAME, warfarin-and combination-treated animals was markedly increased. Increased eNOS expression might represent a compensatory mechanism for the altered NOS activity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Regarding this, it is worth mentioning that the P2Y 2 receptor is expressed by endothelial cells and regulates its nitric oxide release 33 . Interestingly, our research group has recently observed that reduced basal nitric oxide production stimulates arterial media calcification in warfarin‐exposed mice 44 . Thus, arguing that the P2Y 2 receptor might mediate its effects on arterial media calcification by affecting the behavior of endothelial cells or other vascular cells rather than VSMCs.…”
Section: Discussionmentioning
confidence: 99%